Effect of strong electrolytes on edible oils part II: vViscosity of maize oil in 1,4-dioxane in the presence of HCl, NaOH and NaCl at different temperatures - A Rasheed Khan; Rehana Saeed Shama; Fahim Uddin (Journal of Applied Sciences and Environmental Management, 2006)
The effects of strong electrolytes like HCl, NaOH and NaCl on the viscosity of maize oil at various temperatures (298 – 323 K) with the difference of 5 K using 1,4 dioxane as solvent were determined. The viscosity of oil was found to be increased with the increasing concentration of oil and decreases with the rise of temperature. The addition of electrolytes decreases the viscosity of oil although very little which shows that the electrolytes increase the distance between oil molecules and cause the enhancement of rate of flow and the increment of temperature drops the rate of flow of the solutions. Furthermore the concentration of electrolytes increases the viscosity of oil solutions. It is due to the presence of unsaturated ingredients present in the oil and thermal effect. The electrolytes behave as structure breaker. The effect of temperature was also determined in terms of fluidity parameters, energy of activation, latent heat of vaporization, molar volume of oil and free energy change of activation for viscous flow. Journal of Applied Sciences and Environmental Management Vol. 10 (3) 2006: 67-74